Energy polygeneration systems based on LNG-regasification: Comprehensive overview and techno-economic feasibility. (1st December 2020) - Atienza-Márquez, Antonio; Ayou, Dereje S.; Bruno, Joan Carles; Coronas, Alberto
Highlights: Energy polygeneration systems allow harnessing LNG physical exergy efficiently. The techno-economic feasibility of a proposed polygeneration plant is evaluated. The nameplate exergetic efficiency of the polygeneration plant is 42%. The reference time to recover the capital investment of the plant is five years. Equipment costs, electricity and carbon prices determines the economic feasibility. Abstract: Energy polygeneration systems offer an attractive solution to harness efficiently the premium-quality physical exergy contained in Liquefied Natural Gas (LNG) because of its cryogenic temperature. However, this exergetic potential is usually wasted when LNG is regasified. The first part of the paper provides a comprehensive overview regarding applications and technologies, global deployment and main bottlenecks and opportunities related with exergy recovery from LNG-regasification. The second part of the paper is focused on the modelling and techno-economic evaluation of a proposed polygeneration plant. This plant regasifies LNG and squeezes its physical exergy in cascade for the combined production of electric power and refrigeration at low and conventional temperatures. The system aims to increase the efficiency of existing cryogenic power plants but with a moderate additional complexity. The nameplate equivalent electricity of the polygeneration plant proposed is nearly 150 kWh/t-LNG, with an exergetic efficiency of 42%. As a reference, the annual emission of 40 thousand tons of greenhouse gases are avoided and the capital investment may be recovered in a period of 5 years. It is determined the critical impact of the capital cost and economic parameters such as electricity tariffs or carbon taxes on the economic feasibility of this plant.